Quantification of biofilm production on polystyrene by Listeria, Escherichia coli and Staphylococcus aureus isolated from a poultry slaughterhouse - Rodrigues,Laura Beatriz (2010)
This study assessed biofilm formation on polystyrene by Staphylococcus aureus, Listeria monocytogenes, L. welshimeri and Escherichia coli, isolated from a slaughtering plant, grown on tryptic soy broth (TSB) using different glucose concentrations. The tested bacteria produced biofilm in at least one of the concentrations used, and some of them were strong biofilm producers.